PENGEMBANGAN KURIKULUM BERBASIS MADRASAH - Nasir, Muhammad (Hunafa: Jurnal Studia Islamika, 2009)
Education decentralization in Indonesia provides new atmosphere in managing and improving the school curriculum. The reason is that schools are provided with broad apportunity to manage education based on the school-based curricuculum. In other words, the authority to manage education-which was formally under the Centre Government-is recently under the authority of each  school.It is in this context that the Government of  Indonesia through the National Education Department views that there should be  authonomy for schools to managing curriculum.Kata Kunci:    pengembangan kurikulum, Kurikulum Berbasis Madrasah, desentralisasi pendidikan, otonomi sekolah